Personal Branding Psikolog Seto Mulyadi (Kak Seto) di Era Disrupsi Media - Rina Juliastuti; Denik Iswardani Witarti (CARAKA : Indonesia Journal of Communication, 2020)
The rapid technological development has made social media much sought-after in the public. Social media has been widely used in building personal branding. But this is not the case with child psychologist Kak Seto who has no personal account in any of social media platforms, while his activities in the world of children always become an attraction and have news value. The formulation of the problem in this research is how the personal branding of Kak Seto in the era of media disruption. The purpose of this research is to explain the activities of Kak Seto in the context of "a friend of children", reveal what media he uses, and analyze his personal branding in the era of media disruption. This study uses a constructivist paradigm, through qualitative approaches and descriptive research methods. A series of activities he carries out is seen from the conventional types of media he uses. From the results of the analysis in this study, it was proven that conventional media have a strong ability to build the personal branding of Kak Seto. The power of his personal branding which correlates with a good image to meet his expectation as a friend of children has been embedded in the minds of the community.